Analysis of Handling Non-Performing Financing at Indonesian Sharia Bank KCP Muara Bungo - Busriadi, Busriadi; Saputra, M. Yos (Denisya Smart Consulting, 2024)
This research focuses on Handling Non-Performing Financing at Bank Syariah Indonesia KCP Muara Bungo. The type of research used in this research is qualititative research with a descriptive approach. The research object in this study is employees as financing providers from Bank Syariah Indonesia KCP Muara Bungo. The results of the study show that the handling of problematic financing is carried out by Bank Syariah Indonesia KCP Muara Bungo. namely coaching and supervision, restructuring, transfer of assets. This is in accordance with the theory, but in the restructuring stage it is still not in accordance with the theory, the 5C Re-Analysis before carrying out the restructuring was not carried out. The solution to this problem is to carry out a 5C Back Analysis before carrying out a restructuring in order to find out which businesses are eligible and which are not eligible for restructuring